Angus and the cat - Flack, Marjorie, 1897-1958. ([New York] : Farrar, Straus and Giroux, 1997)
Angus the Scottie dog spends three days chasing the new cat that has come to live at his house, but when the cat disappears, Angus misses his new friend.
"A Sunburst book."
2.5
K-3
K-3
Book Links (A.L.A.)
AD 390
Keywords: Dogs -- Juvenile fiction; Cats -- Juvenile fiction; Friendship -- Juvenile fiction; Dogs -- Fiction; Cats -- Fiction; Friendship -- Fiction; Dogs -- Fiction; Cats -- Fiction; Friendship -- Fiction